Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran untuk Meningkatkan Minat Belajar Siswa di SD Bakalan - Putra, Lovandri Dwanda; Denanda, Fiola; Pradana, Hendra Wahyu; Azahwa, Mayda Nurmala; Cynthia, Devi (LPPM Institut Pendidikan Nusantara Global, 2024)
The current era of technology is a new innovation in social life. Almost all human activities are involved with technology. The development of technological has recently progressed very rapidly. Over time, technology has penetrated various sectors, including the education sector. The purpose of this research is to find out whether SD Negeri Bakalan has utilized technology-based learning media. The research method used is a qualitative method by means of interviews to obtain information about whether the elementary school has implemented technology-based learning media. The results of this research are that at SD Negeri Bakalan, which we interviewed one of the teacher, has implemented technology-based learning media, namely the Canva application and using PowerPoint as a learning media. The utilization of learning media is not all subjects can use PowerPoint, only subjects such as IPAS can use this learning media. The use of PowerPoint learning media can increase students' enthusiasm in participating in learning.